Qualidade de vida no trabalho: revis??o de alguns modelos - Nunes, Rinaldo Aparecido (2004)
This study will investigate the Human Resource Management function as a tool for the company to reach its goals. The companies should consider their employees' health under a new perspective: to promote life quality at work. This is a very relevant fact for the companies as it reflects directly on competition. Moreover, to invest in employees' health means to acquire a more pleasurable atmosphere at work. The models presented in this study show us how important it is for the company to value their employees by investing in training and caring about their physical and psychological conditions. These procedures will create opportunities to make them tuned in the company purposes. Hence, this study concludes that the role of the training in the Human Resources field is one of the most important way for the companies to reach the best results.Therefore, when the companies invest in better life conditions for their employees and for the enterprise, the companies are then indirectly assuring better quality and production.